Inscription, David Sassoon Clocktower - Ghosh, Ayan (2023)
The name of David Sassoon is inscribed over the arch on the ground floor. He had donated a large sum (₹ 30,000) for building the clock tower. A Baghdadi Jew, David Sassoon (1792–1864) funded many educational institutions in Mumbai. Various charity trusts, that continue to exist today, were funded, by and named after him and other members of the Sassoon family.